Structural basis of the radical pair state in photolyases and cryptochromes. Issue 31 (30th March 2022) - Cellini, Andrea; Shankar, Madan Kumar; Wahlgren, Weixiao Yuan; Nimmrich, Amke; Furrer, Antonia; James, Daniel; Wranik, Maximilian; Aumonier, Sylvain; Beale, Emma V.; Dworkowski, Florian; Standfuss, Jörg; Weinert, Tobias; et al.
Abstract : The structural response of the drosophila (6-4) photolyase to photoinduced electron transfer along a chain of tryptophans is revealed using a serial crystallographic snapshot of the protein in its radical pair state. Abstract : We present the structure of a photoactivated animal (6-4) photolyase in its radical pair state, captured by serial crystallography. We observe how a conserved asparigine moves towards the semiquinone FAD chromophore and stabilizes it by hydrogen bonding. Several amino acids around the final tryptophan radical rearrange, opening it up to the solvent. The structure explains how the protein environment stabilizes the radical pair state, which is crucial for function of (6-4) photolyases and cryptochromes.